Cost analysis and cost effectiveness of a subsidized community supported agriculture intervention for low-income families - Jennifer A. Garner; Karla L. Hanson; Stephanie B. Jilcott Pitts; Jane Kolodinsky; Marilyn H. Sitaker; Alice S. Ammerman; Donald Kenkel; Rebecca A. Seguin-Fowler (BMC, 2023)
Abstract Background The food system has a dynamic influence on disparities in food security and diet-related chronic disease. Community supported agriculture (CSA) programs, in which households receive weekly shares of produce from a local farmer during the growing season, have been examined as a possible food systems-based approach for improving diet and health outcomes. The purpose of this study was to estimate the cost of implementing and participating in a multi-component subsidized community supported agriculture intervention and calculate cost-effectiveness based on diet and food security impacts. Methods Using data from the Farm Fresh Foods for Healthy Kids (F3HK) randomized controlled trial in New York, North Carolina, Vermont, and Washington (n = 305; 2016-2018), we estimated programmatic and participant costs and calculated incremental cost-effectiveness ratios (ICERs) for caregivers' daily fruit and vegetable (FV) intake, skin carotenoids, and household food security from program and societal perspectives. Results F3HK cost $2,439 per household annually ($1,884 in implementation-related expenses and $555 in participant-incurred costs). ICERs ranged from $1,507 to $2,439 per cup increase in caregiver's FV intake (depending on perspective, setting, and inclusion of juice); from $502 to $739 per one thousand unit increase in skin carotenoid score; and from $2,271 to $3,137 per household shifted out of food insecurity. Conclusions Given the known public health, healthcare, and economic consequences of insufficient FV intake and living in a food insecure household, the costs incurred to support these positive shifts in individual- and household-level outcomes via a F3HK-like intervention may be deemed by stakeholders as a reasonable investment. This work helps to advance a critical body of literature on the cost-effectiveness of subsidized CSAs and other economic and food system interventions for the sake of evidence-based allocation of public health resources. Trial registration : ClinicalTrials.gov. NCT02770196. Registered 5 April 2016. Retrospectively registered. https://www.clinicaltrials.gov/ct2/show/NCT02770196 .